2018
DOI: 10.3168/jds.2018-15058
|View full text |Cite
|
Sign up to set email alerts
|

Effects of oral administration of acidogenic boluses at dry-off on performance and behavior of dairy cattle

Abstract: The aim of this study was to evaluate the potential of oral acidogenic mineral boluses (196 g) containing anionic salts to facilitate the transition from lactation to the dry stage by inducing a mild and temporary metabolic acidosis at dry-off. In experiment 1, 84 lactating cows were randomly allocated to 1 of 3 treatment groups consisting of an oral administration of 0, 1, or 2 boluses 5 d before dry-off to evaluate the effects on milk production. In experiment 2, 16 lactating cows were involved in a crossove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 54 publications
1
7
0
Order By: Relevance
“…Antibiotic dry cow therapy (DCT), teat sealants, and changes in cows' housing are also applied for drying-off. Furthermore, drying-off can be supported by pharmaceuticals such as dopamine agonists that inhibit prolactin release (Lacasse et al, 2019), casein hydrolysates (Ponchon et al, 2014), chitosan hydrogels (Lanctôt et al, 2017), and acidogenic mineral boluses that induce transient metabolic acidogenesis (Maynou et al, 2018). However, these compounds are not commonly commercially available.…”
Section: Introductionmentioning
confidence: 99%
“…Antibiotic dry cow therapy (DCT), teat sealants, and changes in cows' housing are also applied for drying-off. Furthermore, drying-off can be supported by pharmaceuticals such as dopamine agonists that inhibit prolactin release (Lacasse et al, 2019), casein hydrolysates (Ponchon et al, 2014), chitosan hydrogels (Lanctôt et al, 2017), and acidogenic mineral boluses that induce transient metabolic acidogenesis (Maynou et al, 2018). However, these compounds are not commonly commercially available.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the strategies that have been investigated include a decrease in the quality or quantity of the feed offered to cows in the weeks before dry-off ( Odensten et al, 2005 ; Ollier et al, 2014 ), decreased milking frequency and gradual cessation of milking ( Tucker et al, 2009 ), and the use of pharmacological agents (e.g., casein hydrolysate and prolactin-release inhibitors; Ponchon et al, 2014 ; Bach et al, 2015 ). The use of acidogenic boluses in late-lactation cows has recently been demonstrated to decrease milk yield of high-producing dairy cows, resulting in lower udder pressure, particularly in the first 2 d after dry-off ( Maynou et al, 2018 ).…”
mentioning
confidence: 99%
“…The administration of acidogenic boluses containing ammonium chloride, a strong acidifying agent, leads to a temporary state of metabolic acidosis ( Maynou et al, 2018 ). Severe metabolic acidosis has been associated with decreased rumination time ( DeVries et al, 2009 ), whereas mild metabolic acidosis, such as that observed when feeding diets with negative dietary cation-anion differences ( Goff et al, 2020 ), has not.…”
mentioning
confidence: 99%
See 2 more Smart Citations